Is Chlamydia pneumoniae a risk factor for peripheral atherosclerosis? - Üstünsoy, Haşim; Sivrikoz, Cumhur; Sirmatel, Fatma; Bakir, Kemal; Burma, Oktay; Kazaz, Hakki (Asia Publishing Exchange Pte Ltd, 2007)
Seroepidemiological studies have shown a relationship between Chlamydia pneumoniae and coronary atherosclerosis. It is not clear whether Chlamydia pneumoniae is also a risk factor for peripheral atherosclerosis. Chlamydia pneumoniae antibodies were measured by a microimmunofluorescence method in 75 patients who underwent surgery for peripheral atherosclerosis, and the seroprevalence was compared with that in the normal population. Chlamydia pneumoniae immunoglobulin-G seroprevalence was 80% in the study group vs. 40% in controls. More foam cells were noted on light microscopy in atherosclerotic plaques from the infected patients. The 60 infected patients were divided into: group A (n = 35) given both anti-chlamydial and antiplatelet agents for 1 year; and group B (n = 25) given antiplatelet therapy only. The groups were compared on the basis of clinical findings, ankle-brachial index, and antibody titers. Decreasing Chlamydiapneumoniae immunoglobulin-G seroprevalence in group A correlated significantly with increasing ankle-brachial index and improvement in clinical findings. It was concluded that Chlamydia pneumoniae may be a risk factor for peripheral atherosclerosis.
Keywords: acetylsalicylic acid; azithromycin; immunoglobulin A; immunoglobulin G; immunoglobulin M; adult; aged; ankle brachial index; antibody titer; article; atherosclerosis; atherosclerotic plaque; bypass surgery; chlamydiasis; Chlamydophila pneumoniae; clinical assessment; combination chemotherapy; controlled study; drug dose reduction; foam cell; human; immunofluorescence; major clinical study; microscopy; monotherapy; peripheral occlusive artery disease; risk factor; seroprevalence